DUGAAN INSIDER TRADING OLEH PERUSAHAAN JOUSKA FINANSIAL INDONESIA BERDASARKAN HUKUM PASAR MODAL - Novika Andriani; Dian Purnamasari (Reformasi Hukum Trisakti, 2023)
The capital market forbids the practice of insider trading. The management of investment funds by PT Jouska Financial Indonesia resulted in a loss for the client in this instance. Allegations of insider trading by the directors of PT Jouska Financial Indonesia were the cause of the customer's loss. The issue is whether the PT Jouska Financial Indonesia directors' acts can be characterized as insider trading. The study methodology is normative and is supported by primary data collected through interviews and secondary data. In this study, interviews and literature reviews were used to obtain data. Qualitative data analysis was used, and deductive reasoning was used to get results. According to the letter of employment between PT Jouska Financial Indonesia and the customer, it is stated that the company can manage its customer's funds through investment into the capital market with the existence of an RDI opening clause. Furthermore, based on the derivation of Article 95 UUPM, the existence of insider trading can be seen from the relationship between Aakar Abyasa Fidzuno, as the main director and the issuer, the existence of material insider information which can be seen in the agreement between Aakar and the issuer on March 20 2019 and the existence of securities trading transactions in PT Jouska Financial Indonesia's customer portfolio.